Understanding and Improving Software Build Teams - Phillips, Shaun; Zimmermann, Thomas; Bird, Christian; Zimmermann, Tom (Proceedings of the 36th International Conference on Software Engineering (ICSE 2014), 2014)
Build, creating software from source code, is a fundamental activity in software development. Build teams manage this process and ensure builds are produced reliably and efficiently. This paper presents an exploration into the nature of build teams—how they form, work, and relate to other teams—through three multi-method studies conducted at Microsoft. We also consider build team effectiveness and find that many challenges are social, not technical: role ambiguity, knowledge sharing, communication, trust, and conflict. Our findings validate theories from group dynamics and organization science, and using a cross-discipline approach, we apply learnings from these fields to inform the design of engineering tools and practices to improve build team effectiveness